2001
DOI: 10.1097/00005537-200111000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Microbiology of Normal External Auditory Canal

Abstract: Turcellaotitidis and A. otitidis were present with a much higher frequency than previously described, lending evidence that they be considered normal otic flora. Corynebacterium auris, previously reported only in children, was isolated from normal adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
98
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 14 publications
(16 reference statements)
7
98
0
12
Order By: Relevance
“…Similarly, we were able to isolate bacteria from 75.5% of the patients with CSOM. In addition to pathogenic bacteria, the normal flora that always exist in the exter- nal auditory canal include S. auricularis, S. epidermidis, S. capitis, and Corynebacterium [10,11] . We found that the rates of isolation of pathogenic bacteria, including PA, MRSA, and MSSA, were high.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we were able to isolate bacteria from 75.5% of the patients with CSOM. In addition to pathogenic bacteria, the normal flora that always exist in the exter- nal auditory canal include S. auricularis, S. epidermidis, S. capitis, and Corynebacterium [10,11] . We found that the rates of isolation of pathogenic bacteria, including PA, MRSA, and MSSA, were high.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies, however, have reported the isolation or detection of A. otitis and/or C. otitidis in the outer ear canals and nasopharynges of healthy individuals (6,12,29). Using a PCR assay specific for A. otitis, Durmaz et al (6) detected the presence of this microbe in 4 of 50 (8%) nasopharynx swabs and 3 of 95 (3%) outer ear canal swabs.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, one of the seven positive swabs was obtained from a child with no symptoms of chronic otitis media (1 of 23 healthy individuals), indicating that A. otitis is resident in the ear canals of healthy individuals (6). Stroman et al (29) subjected cerumen and outer ear canal swabs, collected from 164 healthy individuals, to cultivation in order to survey the normal microbiota of the ear. Of the 624 total organisms that were characterized, 48 (8%) A. otitis and 74 (12%) C. otitidis isolates were identified (29).…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] In addition, these organisms are present in the healthy external auditory canal, and thus the external auditory canal may be a source of AOE. 32 Some individuals appear more susceptible to AOE on a genetic basis (those with type A blood group). 33 The subspecies of Pseudomonas causing AOE may be different from those causing other Pseudomonas infections.…”
mentioning
confidence: 99%